Fuzzy Fixed-Time Control for Nonaffine Nonlinear Systems with Unknown Hysteresis Inputs - Li, Yan; Zhao, Xuan (International journal of fuzzy systems, 2023)
In this article, the problem of fixed-time adaptive fuzzy control is addressed for a class of nonaffine nonlinear systems subject to unknown backlash-like hysteresis nonlinearities. A command filter-based adaptive fuzzy fixed-time control strategy is presented via combining the backstepping framework with fixed-time control theory. The packaged unknown nonlinearities appeared in the controller design process are estimated by adopting fuzzy logic systems. At the same time, the “explosion of complex” difficulty occurred in conventional backstepping algorithm is eliminated by adopting a command filter technique and corresponding error compensation signals are exploited to alleviate the influence of the errors generated by command filters. It is further shown that the developed controller not only guarantees the boundedness of all the closed-loop system signals, but also makes the output tracking error arrive a small neighbor around the origin within a fixed time. Finally, both theoretical analysis and simulation research are carried out to further test the feasibility of the presented methodology.